Hubungan Pola Jajan Kariogenik dan Kebiasaan Menggosok Gigi Terhadap Kejadian Karies Gigi Molar Pertama Permanen Pada Anak Usia 8-10 Tahun di SDN 01 Gumpang Kecamatan Kartasura, Sukoharjo - Nugroho, Adi; , drg. Ana Riolina, MPH; , drg. Juwita Raditya Ningsih (2015)
Caries is a disease of hard tissue of teeth that is characterized by the occurrence of demineralization in the inorganic and can be continued to organic part so as cause pain. The first permanent molar teeth are teeth that serve to mastication of food, the first permanent molar teeth have deep pits and fissures so many cariogenic food debris attached to the surface of the first permanent molars if not cleaned properly. Cariogenic snacks pattern is habit of eating snacks at school-age children (6-12 years) in consuming foods that are sweet and sticky. Tooth brushing habits can clean the rest of the food that sticks to the surface of the teeth so as to reduce the risk of caries. The purpose of this study was to determine the relationship of cariogenic patterns and tooth brushing habits on the incidence of dental caries of permanent first molars in children aged 8-10 years at SDN 01 Gumpang sub-District Kartasura, Sukoharjo. Research to determine the pattern of cariogenic snacks done by questionnaire, tooth brushing habits by giving questionnaires and simulated brushing teeth. The results of this research showed that there is a significant correlation of cariogenic snacks pattern (p: 0.00, r: 0.553) and tooth brushing habits (p: 0.00, r: - 0.829) against dental caries incidence first permanent molars in children aged 8-10 years in SDN 01 Gumpang sub-District Kartasura, Sukoharjo. These results indicate that the incidence of dental caries in permanent first molars of school-age children still can not be controlled properly, it is necessary to control the consumption of cariogenic foods and counseling brushing teeth properly for the students so they have awareness to maintain oral health.